Pengaruh Model Brain Based Learning (BBL) Terhadap Hasil Belajar Siswa Kelas XI pada Materi Laju Reaksi - Hikmah Hasan Basri; Sri Mulyani Sabang; Minarni Rama Jura (Universitas Tadulako, 2021)
This study aimed to determine the influence of Brain Based Learning (BBL) model toward learning outcomes of chemistry in grade XI at SMA 7 Palu. The method used was a quasi-experiment with pretest-posttest control group design. Sampling was done by purposive with the sample of class XI Science 2 as the experimental class and class XI Science 5 as the control class. Data of students’ learning outcome was tested using non-parametric statistical analysis, i.e the Mann-Whitney test (U-Test). Analysis of the data obtained the value of students’ learning outcomes in the experimental class (x ̅_1) was 89.16 with a standard deviation of 10.96, while in the control class students the (x ̅_2) value was 56.47 with a standard deviation of 11.50. Hypothesis testing obtained a Zcount value was 5.68 which was in the acceptance area of H1, so tha H1 was accepted and H0 was rejected. This mean that the average score of students’ learning outcomes of the experimental class was not the similar to the control class. This study concluded that the Brain Based Learning (BBL) model influenced students’ learning outcomes on reaction rate at SMAN 7 Palu..